Polarizing beam splitter and preparation method and application thereof
By using diamond substrates and high thermal conductivity materials in infrared polarization spectroscopy and combining the design of metallized film layers, the damage caused by temperature rise during infrared laser annealing is solved, and high thermal stability and good optical performance are achieved.
Patent Information
- Application Number
- CN202411514738.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-28
- Estimated Expiration
- 2044-10-29
AI Technical Summary
Existing infrared polarization spectroscopy is prone to laser damage caused by temperature rise during infrared laser annealing, and it is difficult to achieve high extinction ratio and high laser damage threshold.
Diamond is used as the substrate material for the polarization spectrometer, and a polarization spectrometer, a broadband urgency film and a metallized film layer are prepared on the diamond substrate. Through the high thermal conductivity of diamond and the thermal conductivity of the metallized film layer, damage caused by temperature rise is alleviated and optical performance is improved.
Effectively prevent laser damage caused by temperature rise, ensure high thermal stability and good optical performance of polarization spectroscopy, and provide high reliability and low leakage rate vacuum sealing solutions.
Smart Images

Figure BDA0005106385880000072 
Figure BDA0005106385880000081 
Figure HDA0005106385890000011
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of polarization beam splitters, and in particular to a polarization beam splitter and a preparation method and application thereof. Background Art
[0002] The laser annealing process refers to a process method that uses a laser beam to irradiate the semiconductor surface, generating extremely high temperatures locally in the irradiated area to repair crystal damage and eliminate dislocations. It is an indispensable process step in the manufacturing process of very large-scale integrated circuits.
[0003] The integrated circuit manufacturing process places extremely strict demands on laser annealing uniformity. The "pattern effect" during laser annealing—that is, the temperature non-uniformity within the chip caused by differences in light absorption due to the device pattern—severely impacts device performance and yield. Research has shown that using longer-wavelength, polarized infrared lasers incident at the Brewster angle can significantly reduce this pattern effect during laser annealing. Consequently, related infrared laser annealing equipment has become a focus of attention within the semiconductor industry both domestically and internationally.
[0004] Polarization beamsplitters, used to generate high-performance linearly polarized light, are essential core optical components in infrared laser annealing systems. Compared to polarization beamsplitters operating in the visible and near-infrared bands, those operating in the infrared band, especially the long-wave infrared band, experience more pronounced thermal effects after exposure to infrared lasers and have lower laser damage thresholds, making it difficult to achieve high extinction ratios and laser damage thresholds. Summary of the Invention
[0005] The object of the present invention is to provide a polarization beam splitter and a method for preparing the same, wherein the polarization beam splitter has the characteristics of high thermal conductivity, thereby preventing laser damage caused by temperature rise and ensuring good optical performance.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The present invention provides a polarization beam splitter, comprising a diamond substrate 1, a polarization beam splitting film 2 and a first metallized film layer 4-1 located on one surface of the diamond substrate 1, a broadband antireflection film 3 located on the other surface of the diamond substrate 1, and a second metallized film layer 4-2 located on the side of the diamond substrate 1;
[0008] The first metallized film layer 4 - 1 is located at an edge of one side surface of the diamond substrate 1 .
[0009] Preferably, the diamond substrate 1 is double-sided polished, the RMS value of the optical surface is less than 1 / 50λ, and the surface roughness is less than 0.5nm;
[0010] The surface roughness of the side surface of the diamond substrate 1 is less than 1.6 μm.
[0011] Preferably, a primer layer is provided between the diamond substrate 1 and the first metallized film layer 4-1 and between the diamond substrate 1 and the second metallized film layer 4-2;
[0012] The bottom layer is a Ni-Cr alloy layer.
[0013] Preferably, the materials of the first metallized film layer 4-1 and the second metallized film layer 4-2 are independently one or more of gold, copper, chromium and nickel;
[0014] The thickness of the first metallized film layer 4 - 1 and the second metallized film layer 4 - 2 are independently 1.2 to 2.0 μm.
[0015] Preferably, the polarization splitting film 2 comprises a first high refractive index material layer and a first low refractive index material layer stacked and cyclically arranged in sequence, and the innermost layer and the outermost layer of the polarization splitting film 2 are both the first high refractive index material layer;
[0016] The material of the first high refractive index material layer is ZnSe;
[0017] The material of the first low refractive index material layer is BaF2 doped with YbF3.
[0018] Preferably, the thickness of the polarizing beam splitting film 2 is 10-50 μm, and the total number of layers of the polarizing beam splitting film 2 is 31.
[0019] Preferably, the broadband antireflection film 3 comprises a second high refractive index material layer and a second low refractive index material layer stacked and cyclically arranged in sequence, and the innermost layer and the outermost layer of the broadband antireflection film 3 are both layers of the second high refractive index material;
[0020] The material of the second high refractive index material layer is ZnSe;
[0021] The material of the second low refractive index material layer is BaF2 doped with YbF3.
[0022] Preferably, the broadband antireflection film 3 has a thickness of 10 to 50 μm, and the total number of layers of the broadband antireflection film 3 is 39.
[0023] The present invention also provides a method for preparing the polarization beam splitter described in the above technical solution, comprising the following steps:
[0024] After preparing the second metallized film layer 4-2 and the first metallized film layer 4-1 on the side and edge positions of one side surface of the diamond substrate 1 respectively, a polarization splitting film 2 is prepared on the remaining position of one side surface of the diamond substrate 1, and a broadband anti-reflection film 3 is prepared on the other side surface of the diamond substrate 1 to obtain the polarization splitter.
[0025] The present invention also provides the application of the polarization beam splitter described in the above technical solution or the polarization beam splitter prepared by the preparation method described in the above technical solution in the field of infrared laser annealing equipment in the semiconductor chip industry or LPP driven laser light source of EUV extreme ultraviolet lithography system.
[0026] The present invention provides a polarization beam splitter, comprising a diamond substrate 1, a polarization beam splitting film 2 and a first metallized film layer 4-1 located on one side surface of the diamond substrate 1, a broadband anti-reflection film 3 located on the other side surface of the diamond substrate 1, and a second metallized film layer 4-2 located on the side surface of the diamond substrate 1; the first metallized film layer 4-1 is located at the edge of one side surface of the diamond substrate 1.
[0027] Compared with the prior art, the technical solution of the present invention has the following beneficial effects:
[0028] 1) Diamond is used as the substrate material of the polarization beam splitter. Taking advantage of its high thermal conductivity, the heat generated by the laser acting on the film layer and the substrate can be quickly transferred as quickly as possible, thereby alleviating damage to the polarization beam splitter caused by local temperature rise;
[0029] 2) The metallization treatment of the edge of the polarization beam splitter in the present invention allows the mirror body to be integrally welded to a metal tube shell or water-cooling structure in subsequent applications, which not only improves the thermal conductivity, but also provides a high-reliability and low-leakage vacuum sealing solution.
[0030] Furthermore, the present invention improves the optical and mechanical properties of rare earth fluorides by adjusting the materials of the polarization splitting film and the broadband anti-reflection film (by doping rare earth fluorides), and uses them to replace traditional radioactive ThF4 as a low-refractive-index material, which is environmentally friendly. By adjusting the total thickness of the broadband anti-reflection film, the changes in the mirror surface shape caused by the stress of the polarization splitting film can be further offset, thereby maintaining the high surface accuracy of the polarization splitter. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 Schematic diagram of the structure of the polarization beam splitter of the present invention, wherein 1 is a diamond substrate, 2 is a polarization beam splitting film, 3 is a broadband antireflection film, 4-1 is a first metallized film layer, and 4-2 is a second metallized film layer;
[0032] Figure 2 This is a flow chart of the preparation process of the metallized film layer of the present invention;
[0033] Figure 3 The designed spectrum of the polarization splitting film described in Example 1;
[0034] Figure 4 This is the designed spectrum of the broadband antireflection film described in Example 1. DETAILED DESCRIPTION
[0035] like Figure 1 As shown, the present invention provides a polarization beam splitter, comprising a diamond substrate 1, a polarization beam splitting film 2 and a first metallized film layer 4-1 located on one side surface of the diamond substrate 1, a broadband antireflection film 3 located on the other side surface of the diamond substrate 1, and a second metallized film layer 4-2 located on the side surface of the diamond substrate 1;
[0036] The first metallized film layer 4 - 1 is located at an edge of one side surface of the diamond substrate 1 .
[0037] In the present invention, the diamond substrate 1 is preferably double-sided polished. The RMS value of the optical surface shape of the polished surface of the diamond substrate 1 is preferably less than 1 / 50λ, and the surface roughness is preferably less than 0.5nm. The surface roughness of the side surface of the diamond substrate 1 is preferably less than 1.6μm. The present invention does not impose any particular restrictions on the source of the diamond substrate 1; sources familiar to those skilled in the art can be used. In an embodiment of the present invention, the diamond substrate 1 can be prepared by chemical vapor deposition.
[0038] In the present invention, the diamond substrate 1 has a diameter of 50 mm and a thickness of 2 mm.
[0039] In the present invention, the materials of the first metallized film layer 4-1 and the second metallized film layer 4-2 are preferably independently one or more of gold, copper, chromium, and nickel. When the materials of the first metallized film layer 4-1 and the second metallized film layer 4-2 are independently two or more of the above-mentioned specific selections, the present invention does not have any particular restrictions on the ratio of the above-mentioned specific materials, and they can be mixed in any ratio. In an embodiment of the present invention, the materials of the first metallized film layer 4-1 and the second metallized film layer 4-2 are the same and can be gold.
[0040] In the present invention, the thickness of the first metallized film layer 4-1 and the second metallized film layer 4-2 are preferably 1.2 to 2.0 μm. In an embodiment of the present invention, the thickness of the first metallized film layer 4-1 and the second metallized film layer 4-2 can be 1.5 μm.
[0041] In the present invention, the width of the first metallized film layer 4 - 1 may be 2 mm.
[0042] In the present invention, the first metallized film layer 4-1 and the second metallized film layer 4-2 can realize the integrated welding of the polarization beam splitter with the metal tube shell or water-cooling structure in the subsequent application process, which not only improves the thermal conductivity efficiency, but also provides a high-reliability, low-leakage rate vacuum sealing solution.
[0043] In the present invention, a base layer is preferably provided between the diamond substrate 1 and the first metallized film layer 4-1 and between the diamond substrate 1 and the second metallized film layer 4-2. The base layer is preferably a Ni-Cr alloy layer (the molar ratio of Ni and Cr in the Ni-Cr alloy layer is 80:20), and the thickness of the Ni-Cr alloy layer can be 50 nm.
[0044] In the present invention, the central wavelength of the polarization splitting film 2 is preferably 11.0 μm; the polarization splitting film 2 is (HL)^ 15 H is used as the initial film system, giving the optimized target values of Rs ≥ 99.5% and Rp ≤ 0.1%. In the present invention, the polarizing beam splitting film 2 preferably comprises a first high-refractive index material layer and a first low-refractive index material layer stacked in a cyclic arrangement. The innermost and outermost layers of the polarizing beam splitting film 2 are preferably the first high-refractive index material layer; the material of the first high-refractive index material layer is preferably ZnSe. The material of the first low-refractive index material layer is preferably YbF3-doped BaF2. In the present invention, the YbF3 doping content in the YbF3-doped BaF2 is preferably 0.5wt% to 5wt%. The present invention does not impose any specific restrictions on the thickness of each layer in the polarizing beam splitting film 2; thicknesses familiar to those skilled in the art can be used, meeting the total thickness requirements, and ensuring that each layer has a thickness between 10nm and 10μm. In an embodiment of the present invention, the YbF3 doping content in the YbF3-doped BaF2 can be 1.5wt%. The thickness of the polarizing beam splitting film 2 can be 36μm, and the total number of layers can be 31. In the embodiment of the present invention, the central wavelength of the polarization splitting film 2 is 11.0 μm; the polarization splitting film 2 is (HL)^ 15 H is used as the initial film system, and the optimization target values given are Rs ≥ 99.5% and Rp ≤ 0.1%.
[0045] In the present invention, the central wavelength of the broadband antireflection film 3 is preferably 11.0 μm; the broadband antireflection film 3 is (HL)^ 19H is used as the initial film system, and the optimized target value T is ≥ 99.5%. In the present invention, the single-layer thickness of the broadband anti-reflection coating 3 is preferably ≤ 2 μm. The broadband anti-reflection coating 3 preferably comprises a second high-refractive index material layer and a second low-refractive index material layer stacked in a cyclic arrangement, with both the innermost and outermost layers of the broadband anti-reflection coating 3 preferably being layers of the second high-refractive index material. The second high-refractive index material layer is made of ZnSe; the second low-refractive index material layer is preferably made of YbF3-doped BaF2; the YbF3 doping level in the YbF3-doped BaF2 is preferably 0.5 wt% to 5 wt%. The present invention does not impose any specific restrictions on the thickness of each layer in the broadband anti-reflection coating 3; thicknesses familiar to those skilled in the art can be used, provided that the total thickness requirement is met. In an embodiment of the present invention, the YbF3 doping level in the YbF3-doped BaF2 can be 1.5 wt%. The thickness of the broadband anti-reflection coating 3 can be 30.5 μm, and the total number of layers can be 39. In the embodiment of the present invention, the central wavelength of the broadband antireflection film 3 may be 11.0 μm; the broadband antireflection film 3 may be (HL)^ 19 H is used as the initial film system, and the given optimization target value is ≥99.5%; the single-layer film thickness of the broadband antireflection film 3 is ≤2 μm.
[0046] The present invention also provides a method for preparing the polarization beam splitter described in the above technical solution, comprising the following steps:
[0047] After preparing the second metallized film layer 4-2 and the first metallized film layer 4-1 on the side and edge positions of one side surface of the diamond substrate 1 respectively, a polarization splitting film 2 is prepared on the remaining position of one side surface of the diamond substrate 1, and a broadband anti-reflection film 3 is prepared on the other side surface of the diamond substrate 1 to obtain the polarization splitter.
[0048] In the present invention, it is preferred to use a mechanical mask or a semiconductor lift-off stripping process to deposit the second metallized film 4-2 and the first metallized film 4-1 on the side and edge of one side surface of the diamond substrate 1, respectively. In the present invention, the deposition method is preferably resistance evaporation, electron beam evaporation or sputtering. The present invention does not have any special restrictions on the process of the mechanical mask, semiconductor lift-off stripping process, resistance evaporation, electron beam evaporation or sputtering, and can be carried out using a process well known to those skilled in the art. In an embodiment of the present invention, the process of preparing the second metallized film 4-2 and the first metallized film 4-1 can be to use a lift-off process to deposit the second metallized film 4-2 and the first metallized film 4-1 on the side and edge of one side surface of the diamond substrate 1, respectively. The specific process is: after uniformly coating the photoresist on one side surface of the diamond base, exposing and developing, the exposed and developed diamond substrate is mounted, and the vacuum chamber door is closed and the vacuum is evacuated until the background vacuum reaches 8.0×10 -4 Pa, the workpiece disk is turned on to rotate at 20 rpm, and the ion source is turned on to bombard and clean the diamond substrate before plating for 5 minutes. The ion source is then turned off, and metallized film layers are deposited on the positions of the photolithographically developed diamond substrate and on both sides of the diamond substrate using resistance evaporation. A Ni-Cr alloy film is first deposited as a primer to improve the adhesion of the Au film layer to the diamond substrate, followed by the deposition of the Au layer. The resistance evaporation source for the Ni-Cr alloy film is a spiral tungsten filament, with a deposition rate of 6.0 nm / s and a deposition thickness of 50 nm. The resistance evaporation source for the Au layer is a molybdenum boat, with a deposition rate of 5.0 nm / s and a deposition thickness of 1.5 μm. 30 minutes after the preparation is completed, the resulting sample is removed from the vacuum chamber and the photoresist is stripped, resulting in a second metallized film layer 4-2 and a first metallized film layer 4-1 with a thickness of 1.5 μm.
[0049] In the present invention, a polarization splitting film 2 is prepared on the remaining position of one side surface of the diamond substrate 1. Preferably, the high refractive index material layer is prepared by resistance evaporation, and the low refractive index material layer is prepared by electron beam evaporation or resistance evaporation. The present invention does not have any special restrictions on the process of preparing the high refractive index material layer and the low refractive index material layer and the conditions and parameters involved. The conditions and parameters familiar to those skilled in the art can be used. In an embodiment of the present invention, the preparation process of the polarization splitting film 2 can be: deposition by resistance evaporation. The specific process is: the diamond substrate obtained by the preparation of the metallized film layer is mounted, the vacuum chamber door is closed and vacuum is started until the background vacuum reaches 1.0×10 -3Pa, start the workpiece disk rotation, the speed is 10rpm, start the substrate baking heating, the heating temperature is set to 160℃, and when the baking time is 120min, adjust the workpiece disk speed to 20rpm, turn on the ion source to bombard and clean the diamond substrate before plating for 5min, turn off the ion source, and start the deposition of ZnSe and YbF3-doped BaF2. Both materials are deposited using a multi-position rotary resistance evaporation source with deposition rates of 4.0nm / s and 5.0nm / s, respectively. Complete the preparation of the polarization splitting film 2 according to the film structure shown in Table 1. After the preparation is completed, naturally cool to below 80℃ and take it out of the vacuum chamber.
[0050] In the present invention, the broadband antireflection film 3 is preferably prepared on the other side of the diamond substrate 1 by using a resistance evaporation method to prepare a high refractive index material layer, and electron beam evaporation or resistance evaporation to prepare a low refractive index material layer. The present invention does not have any special restrictions on the process of preparing the high refractive index material layer and the low refractive index material layer and the conditions and parameters involved, and the conditions and parameters familiar to those skilled in the art can be used. In an embodiment of the present invention, the preparation process of the broadband antireflection film 3 can be: deposition by resistance evaporation, and the specific process is: the diamond substrate obtained by preparing the metallized film layer and the polarization splitting film is mounted, the vacuum chamber door is closed and vacuum is started until the background vacuum reaches 1.0×10 -3 Pa, start the workpiece disk rotation, the speed is 10rpm, start the substrate baking heating, the heating temperature is set to 160℃, the baking time is 120min, adjust the workpiece disk speed to 20rpm, turn on the ion source to bombard and clean the diamond substrate before plating for 5min, turn off the ion source, and start the deposition of ZnSe and YbF3-doped BaF2. Both materials are deposited using a multi-position rotary resistance evaporation source at deposition rates of 4.0nm / s and 5.0nm / s, respectively. Complete the preparation of the broadband anti-reflection film 3 according to the film structure shown in Table 2. After preparation, naturally cool to below 80℃ and take it out of the vacuum chamber.
[0051] The present invention also provides for the use of the polarization beam splitter described in the above technical solution, or the polarization beam splitter prepared by the above technical solution, in infrared laser annealing equipment in the semiconductor chip industry or in LPP-driven laser light sources for EUV extreme ultraviolet lithography systems. The present invention does not impose any particular limitations on the method of such application, and methods well known to those skilled in the art may be employed.
[0052] The polarization beam splitter provided by the present invention, its preparation method and application are described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0053] Example 1
[0054] A double-sided polished CVD diamond with a diameter of 50 mm and a thickness of 2 mm was used as a diamond substrate, and a metallized film layer (thickness of 1.5 μm, the width of the metallized film layer at the edge of one side of the diamond substrate was 2 mm) was prepared by a lift-off process. The specific preparation process (such as Figure 2 As shown, Au with a purity of 99.99% is used as the metallized film material) as follows: 5 μm of photoresist is uniformly coated on one side of the diamond substrate, and the deposition area of the metallized film layer is exposed and developed. The size of the photoresist coating area after exposure and development is To ensure that the spectroscope has sufficient aperture; the metallized film layer is prepared by resistance evaporation, the diamond substrate after exposure and development is mounted, the vacuum chamber door is closed and vacuum is pumped until the background vacuum reaches 8.0×10 -4 Pa, start the workpiece disk rotation, the speed is 20r / min, turn on the ion source to bombard and clean the diamond substrate before plating for 5 minutes, turn off the ion source, start the deposition of the metallized film layer, use a Ni-Cr alloy film layer as a base to improve the adhesion of the Au film layer to the diamond substrate, the Ni-Cr alloy film uses a spiral tungsten wire as a resistance evaporation source, the deposition rate is 6.0nm / s, and the thickness is 50nm; the Au film layer uses a molybdenum boat as an evaporation source, the deposition rate is 5.0nm / s, and the deposition thickness is 1.5μm. 30min after the preparation is completed, the obtained sample is taken out of the vacuum chamber, and the photoresist is stripped to obtain a second metallized film layer 4-2 and a first metallized film layer 4-1 with a thickness of 1.5μm.
[0055] The polarization beam splitting film is deposited by resistance evaporation. The specific process is as follows: the diamond substrate prepared with the metallized film layer is mounted on the rack, the vacuum chamber door is closed and vacuum is pumped until the background vacuum reaches 1.0×10 -3 Pa, start the workpiece disk rotation, the speed is 10rpm, start the substrate baking heating, the heating temperature is set to 160℃, when the baking time is 120min, adjust the workpiece disk speed to 20rpm, turn on the ion source to bombard and clean the diamond substrate before plating for 5min, turn off the ion source, and start the deposition of ZnSe and BaF2 doped with YbF3. Both materials are deposited using a multi-position rotary resistance evaporation source, with deposition rates of 4.0nm / s and 5.0nm / s respectively. Complete the preparation of the polarization splitting film 2 according to the film structure shown in Table 1. After the preparation is completed, naturally cool to below 80℃ and take it out of the vacuum chamber. The material of the first high refractive index material layer in the polarization splitting film is ZnSe, and the material of the first low refractive index material layer is BaF2 doped with YbF3. The doping amount of YbF3 in the YbF3-doped BaF2 is 1.5wt%; the thickness is 36μm, and the total number of layers is 31. Figure 3 is the design spectrum of the polarization splitting film 2, Figure 3It can be seen that the polarization splitting film has an Rs greater than 99% and an Rp less than 0.1%.
[0056] Table 1 Materials and thickness of each layer of polarization splitting film
[0057]
[0058]
[0059] The broadband antireflection film is deposited by resistance evaporation. The specific process is as follows: the diamond substrate prepared with the metallized film layer and polarization splitter film is mounted on the rack, the vacuum chamber door is closed and the vacuum is pumped down until the background vacuum reaches 1.0×10 - 3 Pa, start the workpiece disk rotation, the speed is 10rpm, start the substrate baking heating, the heating temperature is set to 160℃, the baking time is 120min, adjust the workpiece disk speed to 20rpm, turn on the ion source to bombard and clean the diamond substrate before plating for 5min, turn off the ion source, and start the deposition of ZnSe and YbF3-doped BaF2. Both materials are deposited using a multi-position rotary resistance evaporation source with deposition rates of 4.0nm / s and 5.0nm / s, respectively. Complete the preparation of the broadband anti-reflection film 3 according to the film structure shown in Table 2. After the preparation is completed, naturally cool to below 80℃, take it out of the vacuum chamber, and complete the preparation of the entire polarization beam splitter. The second high refractive index material layer in the broadband antireflection film 3 is made of ZnSe, and the second low refractive index material layer is made of BaF2 doped with YbF3, wherein the doping amount of YbF3 in the YbF3-doped BaF2 is 1.5 wt%. The thickness of the broadband antireflection film 3 is 30.5 μm, and the total number of layers is 39. The thickness of a single layer of the broadband antireflection film 3 is ≤ 2 μm. Figure 4 is the design spectrum of the broadband antireflection film 3, Figure 4 It can be seen that the transmittance of the broadband antireflection film 3 is greater than 99.5%.
[0060] Table 2 Materials and thickness of each layer of broadband antireflection coating
[0061] Serial number Material Film thickness(nm) Serial number Material Film thickness(nm) Serial number Material Film thickness(nm) 1 ZnSe 291.74 14 <![CDATA[BaF2]]> 1155 27 ZnSe 248.7 2 <![CDATA[BaF2]]> 665.89 15 ZnSe 395.76 28 <![CDATA[BaF2]]> 1917.14 3 ZnSe 693.48 16 <![CDATA[BaF2]]> 1555.71 29 ZnSe 126.74 4 <![CDATA[BaF2]]> 1465.36 17 ZnSe 424.46 30 <![CDATA[BaF2]]> 1025.36 5 ZnSe 575.11 18 <![CDATA[BaF2]]> 1418.21 31 ZnSe 217.61 6 <![CDATA[BaF2]]> 801.43 19 ZnSe 523.7 32 <![CDATA[BaF2]]> 355.54 7 ZnSe 266.63 20 <![CDATA[BaF2]]> 438.04 33 ZnSe 298.91 8 <![CDATA[BaF2]]> 1522.32 21 ZnSe 589.46 34 <![CDATA[BaF2]]> 206.25 9 ZnSe 571.52 22 <![CDATA[BaF2]]> 1086.25 35 ZnSe 860.87 10 <![CDATA[BaF2]]> 1215.89 23 ZnSe 607.39 36 <![CDATA[BaF2]]> 1648.04 11 ZnSe 817.83 24 <![CDATA[BaF2]]> 699.29 37 ZnSe 612.17 12 <![CDATA[BaF2]]> 1673.57 25 ZnSe 847.72 38 <![CDATA[BaF2]]> 1787.5 13 ZnSe 270.22 26 <![CDATA[BaF2]]> 310.36 39 ZnSe 339.57
[0062] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.
Claims
1. A polarization beam splitter, characterized in that: It comprises a diamond substrate (1), a polarization splitting film (2) and a first metallized film layer (4-1) located on one surface of the diamond substrate (1), a broadband anti-reflection film (3) located on the other surface of the diamond substrate (1), and a second metallized film layer (4-2) located on the side of the diamond substrate (1); The first metallized film layer (4-1) is located at an edge position of a surface of one side of the diamond substrate (1).
2. The polarization beam splitter according to claim 1, wherein: The diamond substrate (1) is double-sided polished, the RMS value of the optical surface is less than 1 / 50λ, and the surface roughness is less than 0.5nm; The surface roughness of the side surface of the diamond substrate (1) is less than 1.6 μm.
3. The polarization beam splitter according to claim 1, wherein: A primer layer is provided between the diamond substrate (1) and the first metallized film layer (4-1), and between the diamond substrate (1) and the second metallized film layer (4-2); The base layer is a Ni-Cr alloy layer.
4. The polarization beam splitter according to claim 1, wherein: The materials of the first metallized film layer (4-1) and the second metallized film layer (4-2) are independently one or more of gold, copper, chromium and nickel; The thickness of the first metallized film layer (4-1) and the second metallized film layer (4-2) are independently 1.2 to 2.0 μm.
5. The polarization beam splitter according to claim 1, wherein: The polarization splitting film (2) comprises a first high refractive index material layer and a first low refractive index material layer which are sequentially stacked and cyclically arranged, and the innermost layer and the outermost layer of the polarization splitting film (2) are both the first high refractive index material layer; The material of the first high refractive index material layer is ZnSe; The material of the first low refractive index material layer is BaF2 doped with YbF3.
6. The polarization beam splitter according to claim 5, characterized in that: The thickness of the polarization splitting film (2) is 10 to 50 μm, and the total number of layers of the polarization splitting film (2) is 31.
7. The polarization beam splitter according to claim 1, wherein: The broadband anti-reflection film (3) comprises a second high refractive index material layer and a second low refractive index material layer which are sequentially stacked and cyclically arranged, and the innermost layer and the outermost layer of the broadband anti-reflection film (3) are both the second high refractive index material layer; The material of the second high refractive index material layer is ZnSe; The material of the second low refractive index material layer is BaF2 doped with YbF3.
8. The polarization beam splitter according to claim 7, wherein: The thickness of the broadband anti-reflection film (3) is 10 to 50 μm, and the total number of layers of the broadband anti-reflection film (3) is 39.
9. The method for preparing a polarization beam splitter according to any one of claims 1 to 8, characterized in that: The following steps are involved: After preparing a second metallized film layer (4-2) and a first metallized film layer (4-1) on the side surface and the edge position of one side surface of a diamond substrate (1), respectively, a polarization beam splitter film (2) is prepared on the remaining position of one side surface of the diamond substrate (1), and a broadband anti-reflection film (3) is prepared on the other side surface of the diamond substrate (1), thereby obtaining the polarization beam splitter.
10. Application of the polarization beam splitter according to any one of claims 1 to 8 or the polarization beam splitter prepared by the preparation method according to claim 9 in the field of infrared laser annealing equipment in the semiconductor chip industry or LPP driven laser light source of EUV extreme ultraviolet lithography system.
Citation Information
Patent Citations
Yb, Gd co-doped barium fluoride crystal and preparation method thereof
CN101864596A
Gallium oxide and diamond wafer based on metal bonding layer and bonding method thereof
CN116084024A
Multilayer film for visible-near infrared hyperspectrum and intermediate infrared stealth
CN116840946A
Multi-layer film compatible with full-infrared band stealth and dual-band radiation heat dissipation
CN117111189A
High-power semiconductor laser and packaging method thereof
CN117650424A
Cited By
Dual-band anti-reflection zinc selenide metallized light window and preparation method thereof
CN120813127A